2019
DOI: 10.1021/acsaelm.9b00766
|View full text |Cite
|
Sign up to set email alerts
|

Sn-Doped CdS Nanowires with Low-Temperature Lasing by CW-Laser Excitation

Abstract: Sn-doped CdS nanowires, with the inside coexisting Sn(II)S, Sn 2 (III)S 3 , and Sn(IV)S 2 identified by in situ Raman and XPS spectra, are grown via a simple thermal evaporation deposition technique. Its room-temperature photoluminescence (PL) spectrum shows a broad in-gap emission band out of different Sn dopants which is also superposed by a series of weak modes from a microcavity due to the wire size and its structure, besides the CdS band-edge emission and a side-band emission due to SnS 2. The ratio of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Not many reports exist in the literature on emission of host CaSnO 3 . Sometimes, Sn 3+ contributes in visible PL, as reported elsewhere . We have completely ruled out this possibility by XANES measurement (Figure d) which confirmed the existence of tin as the Sn 4+ ion in CSO.…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Not many reports exist in the literature on emission of host CaSnO 3 . Sometimes, Sn 3+ contributes in visible PL, as reported elsewhere . We have completely ruled out this possibility by XANES measurement (Figure d) which confirmed the existence of tin as the Sn 4+ ion in CSO.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Sometimes, Sn 3+ contributes in visible PL, as reported elsewhere. 57 We have completely ruled out this possibility by XANES measurement (Figure 1d) which confirmed the existence of tin as the Sn 4+ ion in CSO. Zhang et al have reported a broad band in the blue emission region centered around 410 nm.…”
Section: Resultsmentioning
confidence: 55%
“…Similarly, Figure c illustrates the confirmation of the S 2p region and the peak located at 161.51 eV . The Sn 3d spectrum shows one major peak corresponding to Sn 3d 3/2 located at 497.08 eV (Figure d) . The C 1s and O 1s peaks located at 284.76 and 530.60 eV in the survey spectrum are probably due to surface contamination, and these two components have disappeared in the EDS spectrum.…”
Section: Resultsmentioning
confidence: 75%
“…46 The Sn 3d spectrum shows one major peak corresponding to Sn 3d 3/2 located at 497.08 eV (Figure 3d). 47 The C 1s and O 1s peaks located at 284.76 and 530.60 eV in the survey spectrum are probably due to surface contamination, and these two components have disappeared in the EDS spectrum. Moreover, all the observed peaks agreed well with the literature values.…”
Section: Resultsmentioning
confidence: 94%
“…Figure S2 shows the element distribution of the whole sample, which can show the distribution of Sn, Cd, and S on the whole sample, and the dopant content (Sn element) inhomogeneous distribution is still too low to be detected. In our experimental process, SnS 2 is likely to form via the following reactions , …”
Section: Resultsmentioning
confidence: 99%